2023
DOI: 10.3171/2022.10.jns221523
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of intracranial pressure pulse waveform in traumatic brain injury patients: a CENTER-TBI study

Abstract: OBJECTIVE Intracranial pressure (ICP) pulse waveform analysis may provide valuable information about cerebrospinal pressure-volume compensation in patients with traumatic brain injury (TBI). The authors applied spectral methods to analyze ICP waveforms in terms of the pulse amplitude of ICP (AMP), high frequency centroid (HFC), and higher harmonics centroid (HHC) and also used a morphological classification approach to assess changes in the shape of ICP pulse waveforms using the pulse shape index (PSI). METH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Moreover, TBI patients often experience disturbances in cerebral autoregulation which can further amplify this phenomenon. Previous studies have also observed alterations in the shape of ICP pulse waveforms toward more pathologically rounded pulses in TBI patients, even at mean ICP levels below 20 mm Hg ( Hawthorne and Piper, 2014 ; Kazimierska et al, 2021 ; Mataczynski et al, 2022 ; Uryga et al, 2022 ), which suggests that cerebrospinal compliance is often reduced in this population. When intracranial compensatory reserve is depleted (i.e., cerebrospinal compliance is low), pulsatile changes in C a BV appear to be more directly transmitted to the ICP signal.…”
Section: Discussionmentioning
confidence: 85%
“…Moreover, TBI patients often experience disturbances in cerebral autoregulation which can further amplify this phenomenon. Previous studies have also observed alterations in the shape of ICP pulse waveforms toward more pathologically rounded pulses in TBI patients, even at mean ICP levels below 20 mm Hg ( Hawthorne and Piper, 2014 ; Kazimierska et al, 2021 ; Mataczynski et al, 2022 ; Uryga et al, 2022 ), which suggests that cerebrospinal compliance is often reduced in this population. When intracranial compensatory reserve is depleted (i.e., cerebrospinal compliance is low), pulsatile changes in C a BV appear to be more directly transmitted to the ICP signal.…”
Section: Discussionmentioning
confidence: 85%
“…This review includes 43 studies (Czosnyka et al 1988, 1994, 1996, Balestreri et al 2004, Steiner et al 2005, Petrella et al 2008, Schuhmann et al 2008, Shahsavari et al 2008, Smielewski et al 2008, Timofeev et al 2008a, 2008b, Kim et al 2009a, Weerakkody et al 2011, Budohoski et al 2012, Howells et al 2012, Speil et al 2012, Eide and Sorteberg 2013, Haubrich et al 2013, 2016a, 2016b, Pineda et al 2015, Varsos et al 2015, Moyse et al 2016, Calviello et al 2018, Zeiler et al 2018a, 2018b, Jin et al 2019, Sekhon et al 2019, Donnelly et al 2020, Froese et al 2020, Lalou et al 2020, Green et al 2021, Levrini et al 2021, Ziółkowski et al 2021, Liu et al 2022, Uryga et al 2022, Zhu et al 2023 that measured and assessed CC/ CCR continuously using the RAP metric, 11 studies (Piper et al 1999, Raabe et al 1999, Kiening et al 2002, Yau et al 2002, Abdullah et al 2005, Ng et al 2005…”
Section: Resultsmentioning
confidence: 99%
“…Brasil et al [16] found the P2/P1 ratio to increase around 10% after promoting an ICP increase of ~ 4 mm Hg from a baseline of ~ 15 mm Hg in a study of patients with TBI without skull damage. Integrated artificial intelligence-based pulse shape index tracing continuously P2 to P1 proportions has recently been proven to associate both with outcome after TBI and CT findings [65,66]. The time to peak (TTP) is a normalized parameter derived from each pulse triggering up to its highest amplitude [67,68].…”
Section: Icpwmentioning
confidence: 99%